2021
DOI: 10.1111/pedi.13193
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive psychosocial screening in a pediatric diabetes clinic

Abstract: Objective: The ISPAD recommends routine, comprehensive psychosocial screening for adolescents with diabetes. However, few clinics have implemented procedures consistent with these guidelines. This study describes the results of a universal, comprehensive psychosocial screening program in an integrated pediatric diabetes clinic located within an academic medical center.Research Design and Methods: Participants included 232 ethnically diverse adolescents with type 1 diabetes (55.5% female; M age = 14.85; 58.5% H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…52,53 Further, the stepped care approach provided targeted treatment to ensure the right intensity of care. 20 The quantitative findings also showed that almost two thirds of the adolescents in our sample identified three or more concerns related to a variety of domains such as worries, responsibilities, and family conflict, further illustrating the importance of a holistic approach. We found that adolescents with low emotional well-being indicated many of the same concerns compared to the adolescents without low emotional well-being.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…52,53 Further, the stepped care approach provided targeted treatment to ensure the right intensity of care. 20 The quantitative findings also showed that almost two thirds of the adolescents in our sample identified three or more concerns related to a variety of domains such as worries, responsibilities, and family conflict, further illustrating the importance of a holistic approach. We found that adolescents with low emotional well-being indicated many of the same concerns compared to the adolescents without low emotional well-being.…”
Section: Discussionmentioning
confidence: 51%
“…14,15 While some diabetes clinics have started to implement routine psychosocial screening during regular visits, [16][17][18][19] there continues to be a need for evidence-based models to support the integration of mental health care into diabetes outpatient clinics. 11,12,20 Implementing routine psychosocial screening into existing or new care models requires practice change and can impact clinic and healthcare provider workloads and workflows. 10,21 Generally, when mental health problems are identified by diabetes clinicians, treatment is generally deferred to mental health specialists who often are not part of the diabetes inter-professional team and might not be aware of the nuances related to adolescent T1D experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Also displayed in Fig. 1 , psychology consultation rates consistently corresponded to psychosocial screener completion rates, which is unsurprising given that many consultations are scheduled in response to elevated scores on the screener (Brodar et al, 2021 ). Thus, consultation rates also began to decline prior to the shift to telehealth (30% in December to 20% in February).…”
Section: Resultsmentioning
confidence: 80%
“…In May 2018, our clinic adopted routine psychosocial screening procedures. This change corresponded to a 24.9% increase in psychology consultation rates within the clinic over the following 10 months, with consultations specifically for mental health concerns (versus diabetes management or health behavior-related issues) increasing by 71.9% (see Brodar et al, 2021 , for details). The screening protocol included measures of life satisfaction, depression and suicide risk, anxiety, eating disorders, and diabetes-specific measures of self-management behaviors, family conflict, stress, and intrinsic motivation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation